Landslide Resistant Disaster Mitigation Education to Increase the Knowledge of Destana Volunteers - Rahmayanti, Yeni Nur; Novitayanti, Eka; Pramudita, Fadma Aji; Anonyma, Pipi (Asosiasi Profesi Multimedia Indonesia, 2024)
The purpose of this service is to determine the level of knowledge of volunteers in carrying out landslide disaster mitigation. Disaster mitigation is an effort that can be made to reduce the risk of disasters either through physical development. Disaster management volunteers are volunteers who carry out relief activities when a natural disaster occurs, including evacuation, rehabilitation and counseling which has an important role for disaster victims. Its role is quite significant in emergency response, as well as in the speed and enthusiasm of disaster management actions. Matesih District, Karanganyar Regency is an area that has varying slopes ranging from 15 – 30% slope with quite high rainfall every year. In 2024 there will be 4 landslides in Matesih. Matesih District is dominated by steep slopes and experiences high rainfall. This condition causes extensive erosion, weathering and landslides. The service method is carried out by providing education to volunteers before providing the education through a pre-test and after providing the education during the post-test. As many as 30 volunteers attended the outreach event regarding landslide disaster mitigation. with various complex problems. The results can be seen through sessions providing material, discussions and mini simulations regarding landslide disaster preparedness. Volunteers participate actively, especially in discussion sessions with facilitators, this forms the awareness and responsiveness of volunteers in dealing with landslide disaster situations that may occur in their environment. The results obtained were that volunteers were able to know well what to do in the face of a landslide disaster.